OUTBURST CYCLE LENGTH VARIATIONS iN THE DWARF NOVA EM CYGNI - Andronov, I. L; Chinarova, L. L. (Одеські астрономічні публікації, 2017)
The cycle length of the dwarf nova EM Cyg undergoes season-to-season changes which may be interpreted by changes of the accretion rate caused by a solar-type activity of the secondary star. The mean brightness of EM Cyg varies with a cycle of ≈ 3000d and is highly correlated with an amplitude of the sine-like variations. Unexpectedly no correlation was found between the seasonal values of the cycle length and the mean value or amplitude.